2010
DOI: 10.1002/qua.22784
|View full text |Cite
|
Sign up to set email alerts
|

Effective potential energy curves of H2 molecule evolving in a strong time‐dependent magnetic field

Abstract: Evolution of hydrogen molecule, starting initially from its field-free ground state, in a time-dependent (TD) magnetic field of order 10 11 G is presented in a parallel internuclear axis and magnetic field-axis configuration. Effective potential energy curves (EPECs), in terms of exchange and correlation energy, of the hydrogen molecule as a function of TD magnetic-field strength, are analyzed through TD density functional computations based on a quantum fluid dynamics approach. The numerical computations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For example, our study on the H 2 molecule reveals interesting dynamics on the attosecond time scale in the electronic charge‐density of the H 2 molecule 15. The study also revealed distinct features in the effective potential energy curves of the H 2 molecule that can have field‐dependent multiple potential‐well minima 16. However, these TD‐DFT studies employ scalar exchange–correlation (XC) potential and XC energy‐density functional, which depend only on the electronic charge‐density, whereas in the presence of even a weak magnetic field, strong currents are induced to the exposed system.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, our study on the H 2 molecule reveals interesting dynamics on the attosecond time scale in the electronic charge‐density of the H 2 molecule 15. The study also revealed distinct features in the effective potential energy curves of the H 2 molecule that can have field‐dependent multiple potential‐well minima 16. However, these TD‐DFT studies employ scalar exchange–correlation (XC) potential and XC energy‐density functional, which depend only on the electronic charge‐density, whereas in the presence of even a weak magnetic field, strong currents are induced to the exposed system.…”
Section: Introductionmentioning
confidence: 72%
“…In our previous studies based on quantum fluid dynamics (QFD)17, 18 and TD‐DFT, we have investigated the He atom13, 14 and the H 2 molecule15, 16 in a strong TD magnetic field on the order of 10 9 G. These studies reveal not only key similarities with the TI studies but also surprising dynamical features which are not predicted by the TI investigations in static magnetic fields. For example, our study on the H 2 molecule reveals interesting dynamics on the attosecond time scale in the electronic charge‐density of the H 2 molecule 15.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…7 All these methods have been used to study various atomic and molecular systems in strong and superstrong magnetic fields (of the order of 10 13 G), however, only for static time-independent (TI) magnetic fields. Recently, we had carried out studies [8][9][10][11] of atomic and molecular systems in presence of a strong TD magnetic field that revealed a few interesting features in the dynamics of the studied systems, which cannot be predicted using TI investigations involving static magnetic fields. For example, our study 11 of the H 2 molecule in a strong TD magnetic field of the order of 10 9 G, through a TD-DFT and quantum fluid dynamics (QFD) [12][13][14] based approach, predicted a significant feature in the effective potential energy curves that show field-dependent multiple potential-well minima.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we had carried out studies [8][9][10][11] of atomic and molecular systems in presence of a strong TD magnetic field that revealed a few interesting features in the dynamics of the studied systems, which cannot be predicted using TI investigations involving static magnetic fields. For example, our study 11 of the H 2 molecule in a strong TD magnetic field of the order of 10 9 G, through a TD-DFT and quantum fluid dynamics (QFD) [12][13][14] based approach, predicted a significant feature in the effective potential energy curves that show field-dependent multiple potential-well minima. However, these studies based on the TD-DFT did not use any current-density dependent exchange-correlation (XC) potential and XC energy density functional, whereas even in a weak magnetic field, strong currents can build up in the exposed system.…”
Section: Introductionmentioning
confidence: 99%